Word-Formation : an international handbook of the languages of Europe. Volume 5 - Müller, Peter O., 1955-; Ohnheiser, Ingeborg; Olsen, Susan, 1948-; Rainer, Franz, 1957- (Berlin : De Gruyter Mouton, 2016)
This handbook comprises an in-depth presentation of the state of the art in word-formation. The five volumes contain 207 articles written by leading international scholars. The 16 sections of the handbook provide the reader in general articles and individual studies with a wide variety of perspectives. The final section contains 74 portraits of word-formation in the individual languages of Europe and offers an innovative perspective.
XVI. Word-formation in the individual European languages
Elektronická reprodukce.
Keywords: tvoření slov; evropské jazyky; word formation; European languages; příručky; e-knihy online; handbooks and manuals; e-books online